2009
DOI: 10.3329/uhj.v5i1.3436
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ischaemic heart disease with risk factors in different categories of employees of University Grants Commission

Abstract: Coronary artery disease is the major cause of mortality world wide. The potentially modifiable risk factors for coronary artery disease were increased concentrations of low density lipoprotein cholesterol, decreased concentrations of high density lipoprotein cholesterol, hypertension, hyperglycemia, and smoking. This cross sectional study which included all UGC employees was conducted in the department of cardiology of BSMMU between January 2007 and December 2007. Detailed clinical history, family history, lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
0
16
2
Order By: Relevance
“…In this study, the investigators reported that the overall prevalence of IHD was 3.4%, whereas the prevalence in 157 men (4.6%) was approximately twice of that in 290 women (2.7%) 23) . Another study conducted by Ahsan et al revealed that the prevalence of IHD was 17.2% among 163 adult subjects in an urban setting of Dhaka city 24) .…”
Section: Mortality and Morbidity Caused By Cvd In Bangladeshmentioning
confidence: 95%
See 1 more Smart Citation
“…In this study, the investigators reported that the overall prevalence of IHD was 3.4%, whereas the prevalence in 157 men (4.6%) was approximately twice of that in 290 women (2.7%) 23) . Another study conducted by Ahsan et al revealed that the prevalence of IHD was 17.2% among 163 adult subjects in an urban setting of Dhaka city 24) .…”
Section: Mortality and Morbidity Caused By Cvd In Bangladeshmentioning
confidence: 95%
“…A global case-control study of risk factors for early acute myocardial infarction reported that the mean age (51.9 years) for the occurrence of acute myocardial infarction among Bangladeshi population was the lowest amongst all South Asians, and it was 6 years lower compared with the non-South Asians (58.8 years) 17) . A number of studies [23][24][25][26][27] reported the burden of IHD in different contexts and cohorts consisted of Mahmud et al 44) 1989 Urban school 5-18 5011 0.9 per 1000…”
Section: Ischemic Heart Diseasementioning
confidence: 99%
“…Initial ball-and-case metallic valves are out of use now-a-days, majority of the prostheses used today are bileaflet valves. In the recent years, primary angioplasty is being performed in Government 14 , as well as, in private 144 centers.…”
Section: Present Status Of Cardiovascular Care Facilitiesmentioning
confidence: 99%
“…The reported values indication the prevalence of CAD include 0.33% in general population in 1976, 37 between 1.85% and 3.4% in rural 38,39 and 19.6% in urban working professionals. 40,41 Despite marked disparity in values, there seems to be a rising prevalence of CAD in Bangladesh. 2,42 Epidemiology of Periodontal disease Periodontitis is the most common chronic inflammatory disease seen in humans, affecting 20-50% of the population worldwide.…”
Section: (Figure 1)mentioning
confidence: 99%